Acute effects of hyperglycemia and hyperinsulinemia on hepatic oxidative stress and the systemic inflammatory response in rats - Ling, Pei-Ra; Smith, Robert J; Bistrian, Bruce R (Critical care medicine, 2007)
Intensive blood glucose control to a target value of 80-110 mg/dL has been shown to reduce morbidity and mortality in surgical intensive care unit patients. This was attributed predominantly to correction of hyperglycemia, based on multivariate regression analysis. However, the effects of glucose and insulin have not been independently evaluated. This study investigated the development of hepatic oxidative processes and systemic inflammatory response in rats with different levels of induced hyperglycemia and hyperinsulinemia. The effects of a modest increase in blood glucose following glucose infusion at a level adequate to meet energy requirements, hyperinsulinemia induced by a hyperinsulinemic euglycemic clamp with administered glucose in similar amounts, and marked hyperglycemia and hyperinsulinemia secondary to glucose infusion on hepatic oxidative stress and systemic inflammatory response in vivo were examined. Controlled laboratory study. Medical school laboratory. Specific pathogen-free male Sprague-Dawley rats. Blood glucose was monitored over 3 hrs. At the end of study, the serum concentrations of insulin, tumor necrosis factor-alpha, interleukin-1, and alpha1 acid glycoprotein were determined. Malondialdehyde and total glutathione content were measured in the liver. Glucose infusion adequate to provide energy requirements resulted in a modest increase in blood glucose (143+/-8 mg/dL) and hyperinsulinemia (45 microU/mL) and did not induce measurable hepatic oxidative stress or systemic inflammation. A hyperinsulinemic euglycemic clamp (insulin 112+/-9 microU/mL) resulted in evidence of increased oxidative processes in the liver but no change in hepatic antioxidant capacity or evidence of systemic inflammation. When hyperglycemia (approximately 350 mg/dL) and hyperinsulinemia (167+/-9 microU/mL) were induced by excess glucose infusion, rats manifested hepatic oxidative stress, antioxidant depletion, and a mild systemic inflammatory response. Hyperglycemia is a major cause of the systemic inflammatory response. Maintaining normal blood glucose, by avoiding overfeeding and providing insulin therapy when necessary, appears key to minimizing oxidative stress and systemic inflammation when intravenous nutrition is provided.